Protest and Organization in Dictatorial Times: Bank Workers of the City of Buenos Aires (1976–79) - Torres, Juliana (Hispania Nova, 2026)
This article addresses the repressive violence, labor conflict, and the first attempts at union re organization experienced by the banking staff of Buenos Aires during the first years of the civil-military dictatorship (1976-79). From an approach that considers the dimensions of class and gender, it analyzes the changes that occurred in labor conditions and in the modalities of repressive action exercised on the union, as well as the strategies outlined by the workers to confront the conditions imposed by the dictatorship. Likewise, based on a wide range of sources –including publications, archival documents, and oral interviews–, it investigates the situation of bank workers within the union space. In this way, by recovering the agency of the workers, it seeks to shed light on a little-explored period of the history of banking unions in the City of Buenos Aires.
Keywords: banking union; City of Buenos Aires; civil-military dictatorship; repression; labor unrest; female bank workers